Community Resilience to Climate Change in Agricultural Sector (Case Study of Sentolo Subdistrict) - Fitria Nucifera; Widiyana Riasasi; Andung Bayu Sekaranom; Emilya Nurjani (Department of Urban and Regional Planning, Universitas Diponegoro, 2020)
Climate change has become a global issue over last decades. Its impact affects to various aspects of human life. Uncertainty of dry and wet seasons present a consequence to and create losses on agriculture sector. Therefore, resilience to climate change is necessary for farmers. This research aims to identify exposure, sensitivity, and adaptive capacity within the framework of community resilience to climate change in agricultural sector. Parameters used in this research include rainfall variability representing system exposure, landuse and topography representing sensitivity, and farmer’s knowledge and behavior representing adaptive capacity. Secondary data used in this research are daily rainfall data, land use and topographic maps, while primary data obtained by interview using purposive sampling method to measure adaptive capacity of farmers community. We employ trend, spatial, and descriptive analysis. The results show that Sentolo Subdistrict has a relatively high exposure to extreme events both in wet and dry seasons that occurred 5 times in 12 years. However, this high exposure did not affect agriculture sector on Sentolo significantly, both in terms of damages and losses to farmers. It indicates that the sensitivity to climate change in this area is low, while farmers’ community in Sentolo has a high level of adaptive capacity. They have sufficient level of knowledge to climate change, better adjustment to technology and well-managed assets. This interplay shows that the agricultural community in the study area has a relatively high resilience to climate change.